Strategies to Handle Students Who Transfer or Drop Out According to Islamic Teachings - Lutfi Firdausi (CV. Agrapana Media, 2025)
Education is a fundamental right of every learner and an obligation in Islamic teachings aimed at developing human potential comprehensively. However, the phenomena of student transfers (mutasi) and school dropouts remain serious issues in the education sector, affecting the continuity of the learning process and the future of young generations. This study aims to examine the phenomena of student transfers and dropouts from the perspective of Islamic education and to formulate appropriate strategies for addressing them based on Islamic values. The research method used is library research by reviewing various relevant sources, including the Qur’an, Hadith, academic books, and previous studies. The findings indicate that transfers and dropouts are influenced by economic limitations, low learning motivation, lack of family support, and unsupportive social environments. In Islam, every child has the right to receive an education, and school dropout is a condition that contradicts the principle of the obligation to seek knowledge. Islamic values such as ukhuwah Islamiyah (Islamic brotherhood), family responsibility, social justice, and the spirit of learning as an act of worship serve as the foundation for preventive efforts. The strategies proposed include preventive approaches such as strengthening family-based education, fostering Islamic character, and creating a religious school environment, as well as curative approaches including Islamic counseling, adaptation support for transferred students, and social assistance through zakat, infaq, and sadaqah. Therefore, an integrative approach grounded in Islamic teachings is required to effectively and sustainably address these issues.